The complete mitochondrial genome of Glycera chirori Izuka (Annelida: Polychaeta): an evidence of conservativeness between gene arrangement and phylogenesis in Glycera. Issue 2 (3rd July 2019) - Chen, Panpan; Shen, Xin; Cai, Yuefeng; Ji, Nanjing; Li, Yongqi; Ge, Tian; Liu, Shishi
Abstract: The complete mitochondrial genome of Glycera chirori Izuka (Annelida: Polychaeta) was presented, which is a circular molecule of 15, 930 bp nucleotides. It encodes 37 genes, including 13 PCGs, 22 tRNAs, and two rRNAs. The length of non-coding regions is 1428 bp, and the longest one (1346 bp) is speculated as the control region, which is located between trnA and trnL2 and is longer than most species in Glycera . The complete mitogenome of G . chirori Izuka consists of 31.2% A, 23.6% C, 12.9% G, and 32.2% T, which has T vs. A skew (−0.02) and C vs. G skew (−0.29), respectively. Phylogenetic analysis indicates the classification status of G. chirori Izuka and the relationship with other species in Glycera, which is closer with Glycera unicornis and Glycera fallax (bootstrap = 100). By comparisons, the gene arrangement of G. chirori Izuka and other seven species in Glycera are identical and they also cluster together in phylogenetic tree with higher support rate, which indicates the conservativeness between gene arrangement and phylogenetic analysis in Glycera . In conclusion, the complete mitochondrial genome of G. chirori Izuka can provide supportive data for further molecular and evolutionary analysis of Glycera .